2018
DOI: 10.18203/2320-6012.ijrms20183273
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinase-9 (MMP-9) as prospective histopathological and molecular biomarker for oral squamous cell carcinoma

Abstract: Background: Despite the advance of therapeutic approaches, the morbidity and mortality of oral squamous cell carcinoma have not improved significantly. The invasion potential of oral squamous cell carcinoma is conferred by their ability to utilize Matrix metalloproteinase that are produced by the host’s stromal cells. In the present study an effort was made to analyse the role of clinical features and risk factors in the causation of oral squamous cell carcinoma and expression of Matrix metalloproteinase-9 (MM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 9 publications
2
4
0
Order By: Relevance
“…Our study observed a statistically significant relationship while comparing the grades of staining intensity and MMP-9 expression with the development of oral squamous cell carcinoma (Table 3). This observation is consistent with other studies reported by Jose et al 25,26 . Our study showed that MMP-9 was not expressed in normal mucosa among healthy individuals.…”
Section: Discussionsupporting
confidence: 94%
“…Our study observed a statistically significant relationship while comparing the grades of staining intensity and MMP-9 expression with the development of oral squamous cell carcinoma (Table 3). This observation is consistent with other studies reported by Jose et al 25,26 . Our study showed that MMP-9 was not expressed in normal mucosa among healthy individuals.…”
Section: Discussionsupporting
confidence: 94%
“…This established a statistically significant association between a high expression of the marker and the advanced stage of the tumor (p<0.001). These findings are in accordance with studies conducted by Atla B et al [ 14 ] and Sowmya V et al [ 15 ], which showed a significant association between the expression of the protein and an advanced stage of the tumor.…”
Section: Discussionsupporting
confidence: 93%
“…In the study conducted by Atla B et al [ 14 ], 70% of the cases with lymph node metastases had a high expression of the marker, and the remaining 30% had a low expression. Among the cases without lymph node metastases, 82.2% had a low expression, and 17.8% had a high expression of the marker.…”
Section: Discussionmentioning
confidence: 99%
“…Ikebe et al 64 pointed out that MMP-9 overexpression could lead to invasion but not metastasis in oral carcinogenesis. Atla et al 56 reported over expression of MMP-9 in stage III oral tumors. Champatyray et al 65 reported immunoexpression pattern of MMP-9 in different grades of oral squamous cell carcinoma.…”
Section: Resultsmentioning
confidence: 99%
“…54 The expression of VEGF in tumor tissues is directly proportional to the invasion depth of carcinogenesis. 55 Atla et al 56 focused on MMP-9 as an important molecular and histopathological marker of carcinoma and thus could be used as a therapeutic target in oral cancer. A positive correlation between MMP-2 and 9 expression and survival outcome has been reported in several types of cancers.…”
Section: Resultsmentioning
confidence: 99%